PEMANFAATAN BIOTEKNOLOGI FERMENTASI DALAM PEMBUATAN KEFIR AIR KELAPA STRAWBERRY–MINT SEBAGAI INOVASI PANGAN FUNGSIONAL UNTUK MENDUKUNG SDGS 2: KETAHANAN PANGAN - Berliana Nichlah Diah Ayu Putri; Yesika Erliana Putri; Mirna Rafika Dewi; Sa'adatud Daroini Rahmania; Nurul Jadid Mubarokati; Nur Ducha (Jurnal Biogenerasi, 2026)
This study aims to analyze the effect of varying concentrations of strawberry–mint extract on the physicochemical and sensory characteristics of coconut water kefir as an innovative non-dairy functional fermented product. A laboratory experimental design was employed with three treatments: P1 (500 mL), P2 (750 mL), and P3 (1000 mL) of strawberry–mint extract. Sensory evaluation was conducted by 32 untrained panelists using the hedonic method, assessing color, aroma, taste, texture, and overall acceptability. The pH value was measured as a supporting indicator of fermentation quality and safety. Data were analyzed using quantitative descriptive analysis, one-way ANOVA, and Duncan’s Multiple Range Test (DMRT) at a significance level of p < 0.05. The results indicated that the addition of strawberry–mint extract significantly influenced several sensory attributes, particularly color and taste, with P3 achieving the highest panelist acceptance. The pH of all treatments ranged from 3.8 to 4.2, demonstrating optimal fermentation. The combination of coconut water, strawberry, and mint produced a probiotic beverage rich in bioactive compounds, exhibiting favorable sensory quality and offering a lactose-free functional food alternative. This innovation supports the Sustainable Development Goals (SDGs) 2, particularly by promoting the development of value-added local functional foods that contribute to food security.